PENGUATAN KAPASITAS MANAJERIAL UKM BATIK DI KOTA PEMATANG SIANTAR MELALUI PELATIHAN KETERAMPILAN MANAJEMEN PEMASARAN DIGITAL DAN KEUANGAN - Yohan Purnawan; Yeni Trisna Purba; Peronika Sari Br Tarigan (Nusantara Hasana Journal, 2025)
This Community Service Program aims to strengthen the managerial capacity of batik SMEs in Pematang Siantar City through training and mentoring in digital marketing and business financial management. The main problems faced by partners include marketing that is still predominantly offline, inconsistent promotional content, suboptimal use of marketplaces and social media, and disorganized financial records, making it difficult to calculate cost of goods, profit, and cash flow. The intervention was carried out through needs assessment, structured training, hands-on practice (including the creation of business accounts, product catalogs, promotional content, and simple bookkeeping), as well as pre–post evaluation and follow-up actions. The outputs of this program include training modules, simple SOPs for digital marketing, bookkeeping templates (cash, sales, expenses, inventory), and a 30-day action plan for each SME. This program is expected to improve digital literacy, enhance the consistency of financial record-keeping, and strengthen business decision-making capacity, thereby increasing the competitiveness of local batik SMEs.